Transmission and absorption spectra of light waves on graphene-embedded Cylindrical Photonic Quasicrystals - Fernandes, J.A.; Anselmo, D.H.A.L.; Vasconcelos, M.S.; Mello, V.D.; Cottam, M.G. (Optical materials, 2022)
We present a study for the transmission and absorption spectra of light propagating radially in multilayered cylindrical structures where there are concentric layers of dielectric materials with graphene sheets interposed between the layers. The aims are to explore the role of quasiperiodicity in these so-called Cylindrical Photonic Quasicrystals as well as how this property can be modified due to the presence of conducting graphene sheets. Specifically, we employ TiO2 and SiO2 as the two components of the multilayers, and an analysis of the optical properties is made for four distinct aperiodic arrangements of the layers: Fibonacci, Thue–Morse, Double–Period, and Octonacci. The calculations involve solving Maxwell's equations within the layers, subject to modified boundary conditions due to the graphene interfaces. Then a transfer matrix formalism is utilized to deduce the transmission and absorption spectra, which are highly structured and fragmented (with the appearance of frequency bands and gaps) because of the quasiperiodicity. The numerical examples illustrate the influence on the spectra of varying the doping of the graphene sheets. In all generations of the four sequences, it is found that the transmission spectra for the transverse-electric and transverse-magnetic waves tend to develop an increase of asymmetry with respect to frequency variations when the graphene doping is increased. •We analyze the reflectance, transmission and absorption spectra of electromagnetic waves.•The waves propagate in Cylindrical Photonic Quasicrystals (CPQs) with graphene sheets.•We consider four distinct CPQs: Fibonacci, Octonacci, Thue--Morse and Double-Period.•As the chemical potential of graphene increases more rapidly than ℏω0Ω, the first band gap increases correspondingly.•Also, for an increasing mode number m, the Reflectance underwent a shift with respect to frequency, and R → 1.